The Effect of Hydro-Morphology and Habitat Alterations on the Functional Diversity and Composition of Macrophyte Communities in the Large River - Vukov, Dragana; Ilić, Miloš; Ćuk, Mirjana; Igić, Ružica (Frontiers in Environmental Science, 2022)
Aquatic ecosystems are impacted by severe hydrological and hydro-morphological modifications that impact aquatic biodiversity. Rivers are often affected by multiple stressors that simultaneously affect water quality, ecological flow, and habitat and lotic diversity. The identity of individual stressors as specific causes of deterioration might be a helpful tool in water management. We hypothesize that the hydro-morphological stressors induce specific changes of environmental factors that modify the ecological niches of the species constituting the macrophyte communities and that these changes are reflected in the metrics and composition of functional diversity. We have analyzed how trait-based macrophyte functional diversity metrics respond to the hydro-morphological features of a river environment using RDA and Variation Partitioning analysis, and the trait-environment relationship using RLQ and fourth-corner analysis. We have found that the hydro-morphology and habitat alterations do affect diversity metrics of the macrophyte communities in the large rivers. The species functional traits are related to the analyzed environmental factors, although we have expected them to be more sensitive to the hydro-morphological stressors. We consider these results to be the base for further studies on the trait-based ecology of macrophyte communities, as well as on the development of stressor-specific metrics that will improve the assessment procedures of the ecological status in river waterbodies and water management.